Why We Like Podcasts: A Review of Urban Youth's Motivations for Using Podcasts - Nicky Stephani; Maya Rachmawaty; Reni Dyanasari (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2021)
Podcast becomes one of the digital media close with urban youth. People listen to it when they are on their way, doing an assignment, and spending leisure time. As new media content developing nowadays, there is only a little research on podcasts in Indonesia. Research results on podcasts released by the media, research agencies, and streaming platform companies discuss majorly on volume, profile, and access habit of audience. Nevertheless, there is no research investigating the youth's reason for choosing podcasts compared to other media. Hence, this research aimed to identify and present the motivation underlying the urban youth preference on podcasts. This research framework was compiled based on the typology of digital media motivation in uses and gratifications theory, namely educating entertainment or edutainment, storytelling, social, and multi-tasking. This research employed a quantitative and positivist paradigm approach. The research respondents were college students who were still accessing podcasts in the last three months. Eventually, the research result identified a significant effect among four types of motivation for using podcasts. In addition, this research result also proved that the typology model of motivation for using new media could explain the reasons underlying the urban youth in using podcasts. Reviewing the close correlation between the urban youth and podcasts, this research also identified the potential of using podcasts in the education realm.